Aliens, UFOs, and unexplained encounters - Coddington, Andrew (Paranormal investigations., 2018)
Examines UFO sightings through history, investigations into UFOs and aliens, and the scientific possibility of extraterrestrial life. Includes images and illustrations, sidebars, a glossary, sources for further learning, and an index.